2015
DOI: 10.1016/j.bmcl.2015.02.063
|View full text |Cite
|
Sign up to set email alerts
|

AIMing towards improved antitumor efficacy

Abstract: Using the structure-activity relationship emerging from previous reports, and guided by pharmacokinetic properties, new AIMs have been prepared with both improved efficacy against human glioblastoma cells and cell permeability as determined by fluorescent confocal microscopy. We present our first unambiguous evidence for telomeric G4-forming oligonucleotide anisotropy by NMR resulting from direct interaction with AIMs, which is consistent with both our G4 melting studies by CD, and our working hypothesis. Fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Differences in the length of loop regions and position of the loop nucleotides will provide useful tools for designing ligands that would be selective for specific quadruplex structures as has been suggested previously [ 9 , 45 ]. Overall, this work has provided the basis for ongoing co-crystallization studies with the Pu22 c-MYC promoter quadruplex and our set of novel quadruplex ligands, the anthracenyl isoxazole amides (AIMs) [ 33 , 46 ]. These findings will also be of benefit to other researchers in their efforts to target the c-MYC promoter and other therapeutically relevant quadruplex targets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in the length of loop regions and position of the loop nucleotides will provide useful tools for designing ligands that would be selective for specific quadruplex structures as has been suggested previously [ 9 , 45 ]. Overall, this work has provided the basis for ongoing co-crystallization studies with the Pu22 c-MYC promoter quadruplex and our set of novel quadruplex ligands, the anthracenyl isoxazole amides (AIMs) [ 33 , 46 ]. These findings will also be of benefit to other researchers in their efforts to target the c-MYC promoter and other therapeutically relevant quadruplex targets.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we report a high-resolution crystal structure of the major Pu22 quadruplex formed in the human c-MYC promoter and describe several features observed that are potentially important for small molecule binding and quadruplex stabilization. We compare the crystal structure of Pu22 with previously reported solution NMR structures in an effort to inform future design of quadruplex-targeted compounds [ 18 , 32 , 21 , 33 ]. In addition, we have examined the features of the Pu22 crystal structure in conjunction with other quadruplex crystal structures to probe for similar features including positions of ions, water molecules and quaternary interactions.…”
Section: Introductionmentioning
confidence: 99%
“…ISSN 2056-9890 The bicyclic acetal (BA) I can be formed directly via a Criegee-like rearrangement through intermediate IV, or alternatively stepwise via the intermediacy of one electron reorganization to an intermediate diepoxide V (Filatov et al, 2017). Of the ten previous crystal structures of anthryl isoxazoles published by our group (Mosher et al, 1996;Han et al, 2002Han et al, , 2003Li et al, 2006Li et al, , 2008Li et al, 2013;Duncan et al, 2014;Weaver et al, 2015), and the three N-heterocyclic structures solved and disclosed (Weaver et al, 2020), this is the first example we have observed of this rearrangement. Given the observation of this rearrangement it is advisable that the o-pyridyl AIM (II) be stored under an argon atmosphere at low temperature (233 K or below).…”
Section: Chemical Contextmentioning
confidence: 68%
“…We have reported on 3-aryl isoxazole amides (AIMs) with antitumor activity (Han et al, 2009;Weaver et al, 2015) and recently described 10-substituted anthracenes with N-heterocyclic substituents in this series, which possessed robust antitumor activity against both breast and brain tumor cell lines (Weaver et al, 2020). In the course of that study, we attempted to obtain crystals of the 10-o-pyridyl example II by slow evaporation (see Fig.…”
Section: Chemical Contextmentioning
confidence: 99%
“…A comparison with the crystal structures of c-Kit (PDB ID: 4WO2) and human telomeric (PDB ID: 4FXM) quadruplexes as well as other NMR structures [166] emphasized that the conformations of the 5′ end and loop regions were the main discriminatory features to capitalize on when seeking the selective targeting of particular G-quadruplex structures [194]. Co-crystallization studies of MYC Pu22 with novel anthracenyl isoaxole amides (AIMs) G4 ligands developed by the same group are currently ongoing [195,196].…”
Section: Myc Targeting Approachesmentioning
confidence: 99%